2021
DOI: 10.3390/cancers13020231
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Features as Predictive Biomarkers of Response to Immune Checkpoint Inhibitors (ICI) in Metastatic Clear Cell Renal Cell Carcinoma (mccRCC)

Abstract: Renal cell carcinoma (RCC) is the seventh most frequently diagnosed malignancy with an increasing incidence in developed countries. Despite a greater understanding of the cancer biology, which has led to an increase of therapeutic options, metastatic clear cell renal cell carcinoma (mccRCC) still have a poor prognosis with a median five-years survival rate lower than 10%. The standard of care for mccRCC has changed dramatically over the past decades with the emergence of new treatments: anti-VEGFR tyrosine kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 109 publications
0
41
0
Order By: Relevance
“…However, what is even more interesting in our experience is that sPDL-1 levels appear to represent a good surrogate of a response criteria to systemic therapy administered in metastatic CCRCC. In this context, there are many limitations to consider when deciding to treat CCRCC patients with immune checkpoint inhibitors based on the immunohistochemical detection of PD-1/PD-L1 positivity alone [11,27], while the search of markers to anticipate the response to immunotherapy continues [42][43][44]. A new trial (UMIN000027873) has been recently launched to evaluate the therapeutic effect of nivolumamb as a second-line therapy for advanced CCRCC based on the concentrations of serum sPD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…However, what is even more interesting in our experience is that sPDL-1 levels appear to represent a good surrogate of a response criteria to systemic therapy administered in metastatic CCRCC. In this context, there are many limitations to consider when deciding to treat CCRCC patients with immune checkpoint inhibitors based on the immunohistochemical detection of PD-1/PD-L1 positivity alone [11,27], while the search of markers to anticipate the response to immunotherapy continues [42][43][44]. A new trial (UMIN000027873) has been recently launched to evaluate the therapeutic effect of nivolumamb as a second-line therapy for advanced CCRCC based on the concentrations of serum sPD-L1.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Tumor immune microenvironment (TIME) which comprises infiltrated immune cells and immunomodulatory molecules has been revealed highly correlated with cancer progression and ICIs response. [8][9][10] Thus, constructing a prognostic model with the power of evaluating TIME has a great potentiality of predicting clinical outcomes and immunotherapy response in ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…This revealed that PD‐L1 expression was prognostic but not predictive of response to nivolumab. On‐going studies are being carried out to find and select predictive markers, such as tumor mutational burden, 18,19 tumor‐infiltrating lymphocytes 20 or gene expression signatures 21‐25 but due to the complexity of clinical routines, serum markers are readily available for the analysis are currently being investigated. One study conducted recently suggested a rise in eosinophils as a predictive biomarker for ORR, OS, and PFS in metastatic RCC treated with nivolumab 26 …”
Section: Introductionmentioning
confidence: 99%